Perspektif Fazlur Rahman tentang Modernisasi Pendidikan Islam - Ahmad Suryadi; Salahuddin Salahuddin (Madrasah Tsanawiyah DDI Cilellang, 2022)
This study discusses Fazlur Rahman's thoughts which are focused on: (1) the concept of modernization of Islamic education; (2) the variety of modernization of Islamic education; and (3) the implications of his thought on Islamic education in the modern era. This type of research is library research using a philosophical and historical approach. The primary data sources in this study were books written directly by Fazlur Rahman, as well as books relevant to the discussion, while the secondary data in this study were relevant literature materials produced by other thinkers who discussed Fazlur Rahman. The method of data collection in this study used the documentation method and then analyzed using. content analysis techniques. The results show that the concept of modernization of Islamic education according to Fazlur Rahman is that education is the starting point for reform. Any reform model in Islam will never happen without the involvement of education in it. Furthermore, according to Fazlur Rahman, education should be held by prioritizing the freedom of students, because without creative nature, it is difficult for students to develop. The variety of modernization of Islamic education initiated by Fazlur Rahman includes five aspects: educational objectives, education system, educators, students, and educational facilities. The implication of this research is that the modernization of Islamic education leads to the importance of democratizing Islamic education by respecting human potential.